The Effectiveness of RADEC as a Distance Learning Model to Improve the Understanding of Class XI SHS Students on Dynamic Fluid Materials - Salsabila Indana Zulfa; Monica Widyaswari; Ulya Aziza Fitriya (Procedia of Social Sciences and Humanities, 2021)
This study aims to determine the RADEC learning model's effectiveness in improving understanding of dynamic fluid material to XI students of Senior High School (SHS) in distance learning (distance learning). This study used a quasi-experimental method with a nonequivalent control group design. The research population was all students of XI SHS classes, totalling 154 people. The sampling technique used purposive sampling. The sample is XI-3 class as the control group and XI-4 class as the experimental group. The instrument used was a cognitive test. The data analysis technique used descriptive statistics and inferential statistics. The results showed that the two groups' average value is that the pre-test control group was 58.12, and the post-test was 78.13, while the pre-test and post-test experimental group were 76.72 and 87.19. Thus, it can be concluded that the RADEC learning model is more effective than the conventional learning model.